Comparative phosphoproteomic analysis of compatible and incompatible pollination in Brassica napus L. (8th April 2020) - Duan, Zhiqiang; Dou, Shengwei; Liu, Zhiquan; Li, Bing; Yi, Bin; Shen, Jinxiong; Tu, Jinxing; Fu, Tingdong; Dai, Cheng; Ma, Chaozhi
Abstract: Self-incompatibility (SI) promotes outbreeding and prevents self-fertilization to promote genetic diversity in angiosperms. Several studies have been carried to investigate SI signaling in plants; however, protein phosphorylation and dephosphorylation in the fine-tuning of the SI response remain insufficiently understood. Here, we performed a phosphoproteomic analysis to identify the phosphoproteins in the stigma of self-compatible 'Westar' and self-incompatible ' W-3 ' Brassica napus lines. A total of 4109 phosphopeptides representing 1978 unique protein groups were identified. Moreover, 405 and 248 phosphoproteins were significantly changed in response to SI and self-compatibility, respectively. Casein kinase II (CK II) phosphorylation motifs were enriched in self-incompatible response and identified 127 times in 827 dominant SI phosphorylation residues. Functional annotation of the identified phosphoproteins revealed the major roles of these phosphoproteins in plant–pathogen interactions, cell wall modification, mRNA surveillance, RNA degradation, and plant hormone signal transduction. In particular, levels of homolog proteins ABF3, BKI1, BZR2/BSE1, and EIN2 were significantly increased in pistils pollinated with incompatible pollens. Abscisic acid and ethephon treatment partially inhibited seed set, while brassinolide promoted pollen germination and tube growth in SI response. Collectively, our results provided an overview of protein phosphorylation during compatible/incompatible pollination, which may be a potential component of B. napus SI responses.